2011
DOI: 10.1111/j.2040-0209.2011.00376_2.x
|View full text |Cite
|
Sign up to set email alerts
|

Admissible Evidence in the Court of Development Evaluation? The Impact of CARE's SHOUHARDO Project on Child Stunting in Bangladesh

Abstract: Summary Along with the rise of the development effectiveness movement of the last few decades, experimental impact evaluation methods – randomised controlled trials and quasi‐experimental techniques – have emerged as a dominant force. While the increased use of these methods has contributed to improved understanding of what works and whether specific projects have been successful, their ‘gold standard’ status threatens to exclude a large body of evidence from the development effectiveness dialogue. In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Governments must recognise the value of social protection as a ‗hand up, not a hand out' for individual beneficiaries and national prosperity. There is also a growing appetite globally to understand the long-term human and economic gains which nutrition-sensitive social protection offers (Smith et al, 2013). This review contributes to the development of this knowledge base, as a crucial step to encourage the investment of domestic resources for social protection to tackle malnutrition.…”
Section: Executive Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Governments must recognise the value of social protection as a ‗hand up, not a hand out' for individual beneficiaries and national prosperity. There is also a growing appetite globally to understand the long-term human and economic gains which nutrition-sensitive social protection offers (Smith et al, 2013). This review contributes to the development of this knowledge base, as a crucial step to encourage the investment of domestic resources for social protection to tackle malnutrition.…”
Section: Executive Summarymentioning
confidence: 99%
“…Our conclusions highlight the importance of an integrated nutrition-sensitive social protection system. This gives weight to arguments to integrate nutrition, alongside a stand-alone goal (Smith et al, 2013). Many countries have improved nutrition through social protection.…”
Section: Executive Summarymentioning
confidence: 99%
“…Many projects have borne out the evidence that focusing on women's empowerment can have significant changes, not only on women's empowerment, but also on the pathways that improve nutrition. A 2011 review of CARE's SHOUHARDO programme in Bangladesh demonstrated that women's empowerment interventions were the single biggest contribution to a reduction in stunting of 6.5 percentage points a year (Smith et al 2011). The combination of maternal and child health nutrition (MCHN) and empowerment interventions together was stronger -an 8.4 percentage point reduction in stunting, while MCHN interventions alone were less than half as powerful as empowerment interventions on their own.…”
Section: Emergenciesmentioning
confidence: 99%
“…While women are often charged with buying and preparing food for the household, they rarely make decisions about how much money to spend on food, and often do not set the menu. It is estimated that increasing a woman's income by US$10 will have the same health and nutritional impact in the household as increasing a man's income by US$110 (Haddad, Hoddinott and Alderman 1997 (Smith et al 2011). The combination of maternal and child health nutrition (MCHN) and empowerment interventions together was stronger -an 8.4 percentage point reduction in stunting, while MCHN interventions alone were less than half as powerful as empowerment interventions on their own.…”
Section: Gender Empowerment and Women's Equalitymentioning
confidence: 99%